Application of E-learning in Teaching and Learning Statistics for Research - Vathanavong, Thongthiane; Vang , Khammy; Chanthahong1, Khamxay; Lamphaiphanh , Ketsalinh; Pathoumvanh, Phanthamanath; Sisouphanh, Vetmanysay (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The action research methodology was used to this research with the research objectives were to: 1) evaluate the effectiveness (E1/E2) of E-learning on statistics for research; 2) compare students’ learning outcomes before and after class of E-learning in statistics for research, and 3) evaluate students’ satisfaction towards the application of E-learning in teaching-learning process. The sample of the study included 126 students from final year of faculty of Education, Souphanouvong University, who were selected by purposive random sampling. The ADDIE model was research designed to development process of the study, namely: Analysis, Design, Development, Implement and Evaluation. Tests and questionnaires were used as research instruments for data collection. The statistics used included percentage, mean ( ), standard deviation (S.D.) and dependent samples t-test or paired samples t-test was used. The research findings were as: 1) Effectiveness (E1/E2) of E-learning on statistics for research equal 86.70/85.95 that responds to the hypothesis at 0.05 levels with statistical significance; 2) Students’ learning outcomes after class were higher than before class with statistical significance; 3) Students’ satisfaction towards the application of E-learning in teaching-learning process was at a very good level.